Relationship between the functional status constructs and quality of life in COPD - Karoliny dos Santos; Manuela Karloh; Cintia Laura Pereira de Araujo; Andrezza Brognoli D'Aquino; Anamaria Fleig Mayer
Introduction Functional status is an important component of health related quality of life (QOL) in patients with chronic obstructive pulmonary disease (COPD). However there is a lack of studies aiming to evaluate the association between QOL and the different methods for assessing patient´s limitation to perform ADL. Objectives To investigate the association between QOL and functional status, measured by four different instruments: London Chest Activity of Daily Living scale (LCADL), six-minute walking test (6MWT), Glittre ADL-test (TGlittre) and assessment of physical activities in daily living (PADL). Methods Twenty-three patients with COPD, GOLD 2 to 4, were submitted to the following evaluations: spirometry, the Saint George Respiratory Questionnaire (SGRQ), LCADL, 6MWT, TGlittre and assessment of PADL. Pearson or Spearman correlation coefficients were used to verify the association between the variables. Results It was observed correlation between all domains of the SGRQ and the 6MWT, between TGlittre and 'leisure' domain of LCADL; and between the domain 'activity' of the SGRQ with the total score of LCADL (r = 0.53), LCADL% (r = 0.54), 'self care' (r = 0.49) and 'leisure' (r = 0.82). The number of steps correlated with the SGRQ (r = -0.59) and with 'activity' (r = -0.70) and 'impact' (r = -0.52) domains. The standing time correlated with the domain 'activitiy' (r = -0.47) of the SGRQ (p < 0.05 for all). Conclusions Both functional performance and capacity are able to reflect the impact that ADL limitation has on QOL in patients with COPD